Haliotis mykonosensis Owen, Hanavan & Hall, 2001 in the Procida Island (Gulf of Naples) and in the Central Mediterranean Sea, with notes on the Mediterranean HALIOTIDAE - CROCETTA, F.; RISMONDO, S. (Mediterranean Marine Science, 2009)
Seventeen living specimens of Haliotis mykonosensis Owen, Hanavan & Hall, 2001 are reported from the area between the wharf of Sancio Cattolico and Punta di Pioppeto (northern side of Procida Island, Naples) and twenty-six from further Central Mediterranean localities. The species was known up to now from the original description only and this note contributes to a better understanding of its real distribution in the Mediterranean Sea.